Rap1 and Cdc13 have complementary roles in preventing exonucleolytic degradation of telomere 5′ ends - Rikard Runnberg (Nature Portfolio, 2017)
Abstract Telomere DNA ends with a single-stranded 3′ overhang. Long 3′ overhangs may cause aberrant DNA damage responses and accelerate telomere attrition, which is associated with cancer and aging, respectively. Genetic studies have indicated several important players in preventing 5′ end hyper-resection, yet detailed knowledge about the molecular mechanism in which they act is still lacking. Here, we use an in vitro DNA 5′ end protection assay, to study how N. castellii Cdc13 and Rap1 protect against 5′ exonucleolytic degradation by λ-exonuclease. The homogeneous telomeric repeat sequence of N. castellii allows us to study their protection ability at exact binding sites relative to the 5′ end. We find efficient protection by both Cdc13 and Rap1 when bound close to the 5′ end. Notably, Rap1 provides protection when binding dsDNA at a distance from the 5′ end. The DNA binding domain of Rap1 is sufficient for 5′ end protection, and its wrapping loop region is essential. Intriguingly, Rap1 facilitates protection also when its binding site contains 2 nt of ssDNA, thus spanning across the ds-ss junction. These results highlight a role of Rap1 in 5′ end protection and indicate that Cdc13 and Rap1 have complementary roles in maintaining proper 3′ overhang length.